Unsettling Subjectivity across Local, National and Global Imaginaries: Producing an Unhappy Consciousness - Manfred B. Steger; Paul James (Glocalism: Journal of Culture, Politics and Innovation)
This article analyzes the complex and subtle dynamics involved in producing and representing the global-local nexus in everyday life. Its socio-historical context is the destabilization of the current globalization system – and its associated global imaginary – marked by the 2008 Global Financial Crisis, continuing with the populist explosion in the mid 2010s, and climaxing in the 2020 Global Coronavirus Pandemic. But rather than mischaracterizing the current context as “deglobalization”, we describe it as a contemporary intensification of what we have been calling the “Great Unsettling”. This era of intensifying objective instability is linked to foundational subjective processes. In particular, we examine the production of an “unhappy consciousness” torn between the enjoyment of global digital mobility and the visceral attachment to the familiar limits of local everyday life. In doing so, we rewrite the approach to the sources of ontological security and insecurity.